Revisiting Motivational Construct and Learning Preferences in Immersion Context: Does Culture Matter? - Dzulfikri, Dzulfikri (Lingual Journal of Language and Culture, 2022)
Abstract This study is devoted to investigating dynamic motivational construct about learning structures in an immersion context. Because of ever-changing motivational construct in particular driven by learning structures in a new environment, this study assumes that the preferred learning structure which is commonly in favor in their home countries might shift which eventually affects their learning motivation. This study takes place at the language training center of the University of Hawaii at Manoa, USA, and employs a survey.  The research participants are mostly graduate students taking English courses to bridge their language skill.  After doing correlation, the researcher has found several surprising findings. The first finding is that although cooperative learning has the highest contribution to intrinsic motivation, they don’t show any significant correlation (r=.279). On the other hand, competitive learning negatively correlates to intrinsic motivation (r=.-407), suggesting that if competitive learning is enacted, students’ intrinsic motivation even decreases. In terms of learning preference, individualistic learning is favored most which might be affected by learning cultures commonly adopted in graduate programs in the US. Keywords : Self-Determination Theory, learning types, extrinsic and intrinsic motivations.